Endothelial progenitor cells [Endotel progeni̇tör hücreler] - (:unkn) unknown (My University, 2007)
Endothelial progenitor cells (EPCs) are candidate for, to be a treatment option for vascular diseases. It has been proven that EPCs preserve their functions in the postnatal period. EPCs mature in bone marrow, enter peripheral circulation then gather at the site of vascular injury to take a central role in repair process. After they leave bone marrow the cell surface markers of them can change and they can differentiate to mature endothelial cells. At the present time clinical and experimental studies about EPCs fairly increase. But the mechanisms which enable EPCs to mature, migrate and home at the site of injury had not yet been enlightened.
Keywords: Angiogenesis; Endothelial cells; Endothelial progenitor cells; Repair; Vasculogenesis